Longitudinal Mixed-Methods Study: Impact of Social Determinants on Maternal Health Access among Women with Disabilities (Urban vs. Rural) - Elfira Elfira; Achmad Fauzi; Astri Mutiar; Linlin Lindayani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Women with disabilities face persistent inequities in accessing maternal health services, despite legal guarantees of inclusive care. Evidence suggests amplified barriers in rural settings; however, longitudinal data capturing temporal changes and women’s lived experiences remain limited. This study investigated how social determinants shape maternal health access among women with disabilities in urban versus rural settings in Indonesia. Methods: A longitudinal mixed-methods design was applied across two sites in West Java: Bekasi City (urban) and Garut District (rural). A total of 300 women with physical, sensory, or mild intellectual disabilities were followed from early pregnancy to six weeks postpartum. Quantitative data were collected at three time points and analyzed using Generalized Estimating Equations and multilevel logistic regression. Concurrently, 35 participants were purposively recruited for in-depth interviews and focus group discussions, analyzed thematically with NVivo. Data were integrated through triangulation and convergence to explain disparities across the maternal healthcare continuum. Results: Significant urban–rural inequities were found. Urban participants demonstrated higher utilization of ≥4 ANC visits (from 62% to 84%), facility-based deliveries (91%), and postnatal care (77%) than rural participants (ANC from 39% to 56%; delivery 68%; postnatal 52%) (p < 0.05). Key determinants of access included maternal education (AOR = 1.46; 95% CI 1.18–1.81), health insurance (AOR = 1.50; 95% CI 1.20–1.87), family support, economic status, and transportation accessibility. Six qualitative themes revealed reinforcing relational and emotional dynamics: structural barriers, stigma and discrimination, family role, digital divide, coping strategies, and emotional experiences. Conclusion: Women with disabilities experience compounded inequities in maternal healthcare access, particularly in rural areas, driven by intersecting structural, socioeconomic, and relational determinants. Improving accessibility, enhancing disability-sensitive and stigma-free care, and strengthening digital and community support systems are essential to achieve equitable maternal services. Findings inform a new integrative framework for inclusive maternal health, guiding targeted policy and health system interventions in Indonesia and similar low-resource contexts.